Remotely delivered intervention for low back pain: a cochrane systematic review - Oliveira, Lisandra Almeida de (2020)
Background: The growth of mobile telecommunications and Internet access presents new opportunities to reach, support, and treat patients with low back pain (LBP). Recent reports have shown that over half of the world’s population used the Internet in 2018. Remotely-delivered interventions have the potential to increase access to healthcare services, deliver care to rural or isolated areas, offer greater flexibility in scheduling, and potentially saves patient’s time and resources. Thus, we need accurate and robust information on the effectiveness of these interventions for patients with non-specific LBP. Objectives: To evaluate the effectiveness of remotely delivered interventions for patients with non-specific LBP compared to usual care, minimal interventions (e.g., no treatment, waiting-list, advice), or a similar face-to-face intervention on pain intensity and disability. Search Methods: We searched the Cochrane Central Register of Controlled Trials, Medline, Embase, and Physiotherapy Evidence Database (PEDro) up to December 2018. This search will be updated once the protocol is published. We also searched clinical trial register in the ClinicalTrials.gov and WHO International Clinical Trial Registry Platform, and reference lists from previous systematic reviews and included studies. Selection criteria: We included randomized controlled trials enrolling adult participants with non-specific LBP. We considered any health intervention delivered remotely through telecommunication networks or the Internet (e.g., telephone, website, videoconference, apps). The primary outcomes were pain and disability, and secondary outcomes were quality of life, return to work, anxiety, depression, and adverse events. Data collection and analysis: Two reviewers independently performed the screening, extracted data, assessed risk of bias, and quality of the evidence (GRADE). Main results: We included 22 trials (26 records) (n= 4,648). 20 studies evaluated patients with chronic LBP (n=3,077); one study only included acute LBP patients (n=1,343); and one trial included acute and subacute LBP individuals (n=30). Overall, most studies had low risk of bias for timing of outcome assessment, group similarity at baseline, intention-to-treat analysis, selective reporting, and incomplete outcome data. However, all studies had high risk of bias for at least three domains (e.g., blinding of participants, blinding of personnel and blinding of assessor), due to the type of the evaluated intervention. We found very low to low quality evidence that there is a small effect of remotely-delivered interventions compared to usual care for both pain at short (mean difference (MD) -7.0; 95% confidence interval (CI) -13.87 to -0.13; one trial) and intermediate-terms (MD -7.37; 95% CI -10.37 to -4.36; four trials); and a moderate effect size in favor of remotely-delivered interventions for disability at long-term (MD -18.33; 95% CI -21.24 to -15.42; two trials). There is very low to low quality evidence that there is no difference between remotely-delivered interventions and usual care for pain intensity at long- term (MD -3.58; 95% CI -7.36 to 0.20; two trials) and for disability at short (MD -6.67; 95% CI -14.14 to 0.8; one trial) and intermediate-term (MD -4.31; 95% CI -12.03 to 3.41; three trials). Secondary outcomes and the other comparisons are reported through the complete article. Authors’ conclusions: We found very low to low quality evidence that remotely-delivered interventions are more effective than usual care for pain intensity at short- and intermediate-term and for disability at long-term, but no difference was found between both interventions for pain intensity at long- term and for disability at short- and intermediate-term. When compared to minimal interventions, we found very low quality evidence that remotely-delivered interventions are more effective for pain-intensity at short- and intermediate-term and for disability at intermediate-term, but no difference was found between both interventions for disability at short-term. Finally, we found moderate quality evidence that remotely-delivered interventions are more effective than face-to-face interventions for pain-intensity at short-term, but not for disability at short-term, when we found no difference.